Synergistic effects of Fe nanocomplex and nitrophenolate-based biostimulant on growth and physiological performance of tomato seedlings - Vahid Tavallali; Mina Dashti Darvishzadeh (BMC Plant Biology)
Abstract This study examines the dose-dependent synergistic effect of foliar-sprayed iron nanocomplex (Fe NC; 0%, 0.2%, 0.4% w/v) and the nitrophenolate biostimulant Atonik (0, 125, 250 ppm) on tomato (Solanum lycopersicum) seedlings under controlled greenhouse conditions. This novel approach integrates nanotechnology and green biostimulants to enhance plant growth and physiological performance, marking a new direction of interest compared to conventional farming. At 30 days post-treatment, the optimum blend (0.4% Fe NC + 250 ppm Atonik) significantly enhanced growth indicators compared to the control: stem length (+ 84.2%), root length (+ 179.9%), leaf number (+ 190.8%), stem girth (+ 124.1%), and dry weight (+ 173.6%). Physiological improvements included net photosynthesis (Pn: +44.2%), stomatal conductance (Gs: +257.1%), and intercellular CO₂ (Ci: +264.1%), and lower stomatal limitation (Ls: -72.6%). Biochemical estimation showed high concentrations of chlorophyll a (+ 48.7%), chlorophyll b (+ 79.0%), carotenoids (+ 122.2%), soluble proteins (+ 42.2%), and carbohydrates (+ 133.3%). Hormonal regulation showed enhanced gibberellic acid (GA: +60.5%) and auxin (IAA: +74.4%) but decreased abscisic acid (ABA: -38.1% in leaves). Stem nutrient loading was improved by N (+ 75.2%), P (+ 54.6%), K (+ 48.2%), Ca (+ 40.2%), Mg (+ 32.5%), and Fe (+ 93.3%). The aim of this study was to investigate the synergistic action of FeNC and nitrophenolate biostimulant (Atonik) on improving the performance of tomato seedling through combined physiological, biochemical and molecular mechanisms, and formulating an effective nano-biofertilizer mixture for sustainable agricultur. On the basis of these findings, future research would need to investigate the long-term effects of Fe NC and Atonik on fruit production and quality, and their use in various crop species for maximizing agricultural sustainability.